17β-estradiol suppresses H2O2-induced senescence in human umbilical vein endothelial cells by inducing autophagy through the PVT1/miR-31/SIRT3 axis. Issue 227 (March 2023) - Xiang, Xiuting; Wang, Yuyan; Huang, Guanshen; Huang, Jianming; Gao, Mingjian; Sun, Meihua; Xia, Hao; Pare, Rahmawati; Li, Jingjun; Ruan, Yunjun
Abstract: Objective: 17β-estradiol (17β-E2 ) has been implicated in activating autophagy by upregulating SIRT3 (Sirtuin 3) expression, thereby inhibiting the senescence of vascular endothelial cells. Herein, we further examined the molecular mechanisms that regulate SIRT3 expression in 17β-E2 -induced autophagy. Methods: Reverse-transcription-polymerase chain reaction was employed to measure the expression of plasmacytoma variant translocation 1 (PVT1), microRNAs (miRNAs), and SIRT3, and the dual-luciferase assay was used to determine their interaction. Electron microscopy observes autophagosomes, green fluorescent protein-microtubule-associated protein 1 light chain 3 (GFP-LC3) staining, and immunoblot analysis with antibodies against LC3，beclin-1, and P62 were conducted to measure autophagy. Cellular senescence was determined using immunoblot analysis with anti-phosphorylated retinoblastoma and senescence-associated β-galactosidase staining. Results: Women with higher estrogen levels (during the 10–13th day of the menstrual cycle or premenopausal) exhibit markedly higher serum levels of PVT1 than women with lower estrogen levels (during the menstrual period or postmenopausal). The dual-luciferase assay showed that PVT1 acts as a sponge for miR-31, and miR-31 binds to its target gene, SIRT3. The 17β-E2 treatment increased the expression of PVT1 and SIRT3 and downregulated miR-31 expression in human umbilical vein endothelial cells (HUVECs). Consistently, PVT1 overexpression suppresses miR-31 expression, promotes 17β-E2-induced autophagy, and inhibits H2 O2 -induced senescence . miR-31 inhibitor increases SIRT3 expression and leads to activation of 17β-E2 -induced autophagy and suppression of H2 O2 - induced senescence. Conclusion : Our findings demonstrated that 17β-E2 upregulates PVT1 gene expression and PVT1 functions as a sponge to inhibit miR-31, resulting in the upregulation of SIRT3 expression and activation of autophagy and subsequent inhibition of H2 O2 -induced senescence in HUVECs. Highlights: 17β-E2 is associated with an increase in PVT1 expression, then PVT1 binds directly to miR-31 and down-regulates miR-31 expression, while miR-31 binds to SIRT3 and up-regulates SIRT3 expression. 17β-E2 increases the expression of lncRNA PVT1 and PVT1 acts as a sponge to suppress the function of miR-31, which leads to the upregulation of SIRT3 expression.